Islamism and The Challenge of Democratization in Indonesia - Alam, Syariful; Al-Fatih, Sholahuddin; Borsa, Merve Ozkan (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
This article studies the phenomenon of Islamism and its impacts on the process of democratization in Indonesia through a legal normative method by examining some regulations and cases regarding the issue. Extreme Islamic loyalist organizations authorize themselves to judge and decide what is and is not permissible, thereby hampering the development of democratic growth in Indonesia with their frequent interference in the government’s affairs and political parties in decision-making. Democracy in Indonesia is put under threat by these organizations. Studies conducted by several scholars indicate that the socio-religious practices of some Islamic organizations in Indonesia are shifting further away from the goals of democratic values. This research seeks to reveal the involvement of Islamism and its impacts on the process of democratization in the Indonesian government. The research results found that addressing negative images to Islam is not something uncommon, raising concern among Muslims and leaving a big obstacle that the democratization in Indonesia needs to encounter. Keywords: Islam; democracy; political party; religion.